Chemical composition, antioxidant activity, α-glucosidase inhibitory activity, and metabolomic profiling of Dendrobium officinale across diverse growing regions and cultivation modes - He, Shu; Lu, Zhengli; Li, Rurui; Chen, Chun; Fu, Xiong; Kong, Kin Weng; Ismail, Amin; Zhang, Xuechun; Wang, Zhenxing (Elsevier Ltd, 2025)
This study evaluated the chemical composition and bioactivity of nine Dendrobium officinale from three cultivation modes (greenhouse, GC; understory, UC; and simulated wild, SWC) across China. Results demonstrated that UC-cultivated samples exhibited significantly higher flavonoid levels, antioxidant capacity, and α-glucosidase inhibition activity than those under GC/SWC modes. Using GC-IMS and UHPLC-TOF-MS, metabolomic profiling identified 27 volatile and 15 non-volatile biomarkers between different cultivation modes. Further KEGG analysis revealed the key signaling pathways of differential metabolites under different cultivation modes, including aminobenzoate degradation, phenylpropanoid biosynthesis, and phenylalanine metabolism. Overall, the cultivation mode significantly influences the chemical composition and biological activity of Dendrobium officinale, with the UC mode being relatively preferable. However, factors such as geographical distribution also play an important role. These findings provide actionable insights for quality control, cultivation optimization, and functional food/pharmaceutical applications of Dendrobium officinale.